Knowledge and Attitude towards Hypertension Control Efforts by the Elderly at the Bua' Tarrung Elderly Posyandu, Tana Toraja - Baharuddin Baharuddin; Sri Angriani; Adolfina Lukas Siamben; Fera Dwiyanti; Lorensa Oktaviasari (Alliance of Health Activists (AloHA), 2022)
Hypertension is sometimes not accompanied by symptoms, so it needs to be detected early, one of which is regular blood pressure checks. The purpose of this study was to analyze the relationship between knowledge and attitudes of the elderly towards hypertension control efforts at the Bua' Tarrung Posyandu, Lembang Bua' Tarrung Village, Rembon District, Tana Toraja Regency, Indonesia. The design of this study was cross-sectional. The research subjects were 35 elderly who were selected by total population sampling technique. Data on knowledge, attitudes and efforts to control hypertension were collected through filling out a questionnaire, then analyzed using the Chi-square test. The results of the analysis show that the p-value for knowledge was 0.001, while for attitude was 0.000. Furthermore, it was concluded that knowledge and attitudes were related to efforts to control hypertension by the elderly at the Bua' Tarrung Elderly Posyandu. Keywords: elderly; hypertension control efforts; knowledge; attitude